PtII versus PdII-assisted [2 + 3] cycloadditions of nitriles and nitrone. Synthesis of nitrile-derived arylamido platinum(II) and Δ4-1, 2, 4-oxadiazoline palladium(II) complexes. (15th January 2019) - Lasri, Jamal; Eltayeb, Naser Eltaher; Haukka, Matti; Babgi, Bandar A.
Graphical abstract: The reactions of trans -[Pt Cl2 (NCR)2 ] with pyrroline N -oxide afford arylamido platinum(II) complexes trans- [Pt Cl2 {(OCR)NCCH2 CH2 CMe2 NH}2 ] via one-pot reaction involving spontaneous NO bond cleavage. However, the reactions of trans -[Pd Cl2 (NCR)2 ] with pyrroline N -oxide furnish Δ 4 -1, 2, 4-oxadiazoline palladium(II) complexes trans- [Pd Cl2 {NC(R)ONC(H)CH2 CH2 CMe2 }2 ]. Abstract: The reactions of bis(organonitrile) platinum(II) complexes trans -[Pt Cl2 (NCR)2 ] (R = C6 H4 ( p -HCO), CH2 C6 H4 ( p -CH3 )) with pyrroline N -oxide − O + NCHCH2 CH2 CMe2 afford arylamido platinum(II) complexes trans- [Pt Cl2 {(OCR)NCCH2 CH2 CMe2 NH}2 ] (R = C6 H4 ( p -HCO) (1 ), CH2 C6 H4 ( p -CH3 ) (2 )). The spectral data of1 and2 show that the oxadiazoline rings in both cases have opened by a spontaneous NO bond cleavage to form ( Z )- p -formyl- N -(5, 5-dimethylpyrrolidin-2-ylidene)benzamide or ( Z )- N -(5, 5-dimethylpyrrolidin-2-ylidene)-2- p -tolylacetamide ligands, respectively, where the N -atoms of the benzamide or acetamide moieties coordinate to platinum(II) metal centre in trans positions. However, the reactions of bis(organonitrile) palladium(II) complexes trans -[Pd Cl2 (NCR)2 ] with pyrroline N -oxide furnish Δ 4 -1, 2, 4-oxadiazoline palladium(II) complexes trans- [Pd Cl2 {NC(R)ONC(H)CH2 CH2 CMe2 }2 ] (R = C6 H4 ( p -HCO) (3 ), CH2 C6 H4 ( p -CH3 ) (4 )) as the exclusive detected products. Compounds1 –4 have been characterized by IR, 1 H, 13 C NMR spectroscopy, elemental analyses, ESI + -MS and also, in the case of1, by single crystal X-ray diffraction analysis.